2021
DOI: 10.1099/jgv.0.001596
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress specifically inhibits replication of dengue virus

Abstract: Reactive oxygen species (ROS) are chemically active species which are involved in maintaining cellular and signalling processes at physiological concentrations. Therefore, cellular components that regulate redox balance are likely to play a crucial role in viral life-cycle either as promoters of viral replication or with antiviral functions. Zinc is an essential micronutrient associated with anti-oxidative systems and helps in maintaining a balanced cellular redox state. Here, we show that zinc chelation leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…Despite possible antiviral effects of oxidative stress responses (49,50), we observed that ROS inhibition reduced DENV replication in HBMEC. Different mechanisms might explain this phenomenon.…”
Section: Discussionmentioning
confidence: 58%
“…Despite possible antiviral effects of oxidative stress responses (49,50), we observed that ROS inhibition reduced DENV replication in HBMEC. Different mechanisms might explain this phenomenon.…”
Section: Discussionmentioning
confidence: 58%
“…The cells were able to tolerate the virus to the late infection time points, indicating that the virus is persistently replicating inside the Aedes cells, corroborating earlier reports involving other arboviruses such as Sindbis virus, Culex Y virus, and West Nile virus [ 44 , 45 , 46 ]. Viruses are known to induce oxidative stress in host cells, which can have both pro-viral and antiviral impacts on the cells [ 38 , 47 , 48 ]. Either way, this oxidative stress leads to activation of pathways such as apoptosis, as well as downregulation of pathways such as translation, and RNA processing, which is often associated with the formation of RNP complexes called stress granules [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…As part of a central role in the viral replication and oxidative stress, the (dys)function of host mitochondria seems to be an essential element for many viruses ( El-Bacha and Da Poian, 2013 ). For instance, an enhanced level of ROS inhibits DENV infection ( Khan et al., 2021 ). In the ZIKV, this ROS imbalance is associated with mitochondrial and DNA damage in human astrocytes ( Ledur et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the ZIKV, this ROS imbalance is associated with mitochondrial and DNA damage in human astrocytes ( Ledur et al., 2020 ). In both cases, the use of fluorescent probes against free radicals, such as 2′,7′-dichlorodihydrofluorescein diacetate (DCFDA) and dihydroethidium (DHE), were respectively used ( Ledur et al., 2020 ; Khan et al., 2021 ). Perhaps novel studies regarding free radicals production upon CHIKV infection could cast a glance on whether the same phenomena could take place in Aag-2 insect cells.…”
Section: Discussionmentioning
confidence: 99%